Pengembangan Kreativitas Siswa SDN 4 Klatakan Dusun Pecaron, Situbondo, Jawa Timur - Sevia Miranti; Dewi Putri Lestari; Muhammad Sumsanto; Wastu Ayu Diamahesa; Naufara Haini; Ina Eka Andriana; Fadliana Khofiatun; Dina Ahyani; Windi Yuastika; Atiatun Shalehah (Yayasan Tajuk Indonesia, 2024)
This creativity activity is part of the Independent Learning Independent Campus (MBKM) Real Lecture Work (KKN) program of the UNRAM Aquaculture Study Program which aims to stimulate the creativity of elementary school students in grades 1, 2 and 3 in making bracelet handicrafts made from beads and dyeing gypsum in various forms. The destination school is students of SDN 4 Klatakan Dusun Pecaron, Situbondo and the students involved are Grades 1, 2 and 3. School selection is based on close mileage for MBKM KKN students with an Internship location and easy access. Before carrying out student service activities, coordinate with the Principal and classroom teachers regarding permits and the time of implementation of activities. After the permit is given, MBKM KKN students coordinate with the original study program to make a permit related to the time and implementation of activities. The method used in this activity is in 2 ways, namely demonstration of product making and active participation of the students involved. The result obtained is that students are able to hone and improve motor creativity and precision in completing the work they make. The work is made of bracelets made of beads and coloring toys from gypsum materials that have been created. The conclusion obtained by elementary school students was able to follow the instructions and directions from the resource person in following the instructions given in making bracelets made of beads and coloring toys made of gypsum.